2022
DOI: 10.1111/all.15406
|View full text |Cite
|
Sign up to set email alerts
|

Combined assessment of S‐ and N‐specific IL‐2 and IL‐13 secretion and CD69 neo‐expression for discrimination of post–infection and post‐vaccination cellular SARS‐CoV‐2‐specific immune response

Abstract: Background Antibody‐based tests are available for measuring SARS‐CoV‐2‐specific immune responses but fast T‐cell assays remain scarce. Robust T cell‐based tests are needed to differentiate specific cellular immune responses after infection from those after vaccination. Methods One hundred seventeen individuals (COVID‐19 convalescent patients: n = 40; SARS‐CoV‐2 vaccinees: n = 41; healthy controls: n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(134 reference statements)
2
5
0
Order By: Relevance
“…3B right). In line with a reported role for IL‐13 as a specific recall marker [ 27 ], these findings affirm the expression of IL‐13 as a characteristic feature of SARS‐CoV‐2 spike mRNA vaccination. Of note, the MODERNA mRNA vaccinated individuals showed higher IL‐13 levels (p = 0.033) compared to those donors vaccinated with BioNTech/Pfizer mRNA vaccine; however, there were no differences in anti‐HDM or IL‐33 levels between these subgroups (data not shown).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…3B right). In line with a reported role for IL‐13 as a specific recall marker [ 27 ], these findings affirm the expression of IL‐13 as a characteristic feature of SARS‐CoV‐2 spike mRNA vaccination. Of note, the MODERNA mRNA vaccinated individuals showed higher IL‐13 levels (p = 0.033) compared to those donors vaccinated with BioNTech/Pfizer mRNA vaccine; however, there were no differences in anti‐HDM or IL‐33 levels between these subgroups (data not shown).…”
Section: Resultssupporting
confidence: 88%
“…3F ). This particular role of IL‐13 is supported by its recently described function in SARS‐CoV‐2 specific recall responses after infection and vaccination [ 27 ]. As IL‐13 is associated with fast viral clearance [ 29 ] and patients with asthma driven by IL‐13 have a lower risk of death by COVID‐19 [ 30 ], the presence of a persistent concentration of IL‐13 in vaccinated or convalescent individuals may confer an advantage in the case of exposure to SARS‐CoV‐2, e.g.…”
Section: Discussionmentioning
confidence: 93%
“…We observed an increase in CD69+ expression on both total CD3+ and CD3+CD4+ and CD3+CD8+. This finding was supported by previous studies that reported the induction of CD8+CD69+ [ 55 ] and CD4+CD69+ [ 56 ] following vaccination against SARS-CoV-2 [ 57 ]. Here, oEV-S1 treatment via the oral and IN routes induced a significant reduction in CD3+, CD3+CD4+, and CD3+CD8+ co-expressing CD25+, a typical marker of regulatory T cell (T reg).…”
Section: Discussionsupporting
confidence: 87%
“…It induced a robust, early rising (i.e., already 14 days after the first injection) and long-lasting N-specific antibody response. Convacell ® stimulated an N-specific CD4 + and CD8 + T cell response which was characterized by a mixed Th1/Th2 cytokine profile in mice and in NSG mice engrafted with human PBMCs similar to that observed after natural SARS-CoV-2 infection [66]. Importantly, vaccination with Convacell ® protected Syrian hamsters against infection with SARS-CoV-2 as demonstrated by reduced weight loss, lowered virus RNA and ameliorated lung pathology as compared to non-immunized animals.…”
Section: Discussionmentioning
confidence: 78%